2018
DOI: 10.1002/jcp.26859
|View full text |Cite
|
Sign up to set email alerts
|

BMAL1 and CLOCK proteins in regulating UVB‐induced apoptosis and DNA damage responses in human keratinocytes

Abstract: A diverse array of biological processes are under circadian controls. In mouse skin, ultraviolet ray (UVR)-induced apoptosis and DNA damage responses are time-of-day dependent, which are controlled by core clock proteins. This study investigates the roles of clock proteins in regulating UVB responses in human keratinocytes (HKCs). We found that the messenger RNA expression of brain and muscle ARNT-like 1 (BMAL1) and circadian locomotor output cycles kaput (CLOCK) genes is altered by low doses (5 mJ/cm ) of UVB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 54 publications
(104 reference statements)
1
18
0
Order By: Relevance
“…The effect of UVB rays on the DNA damage of skin cells was evaluated in association with a pre-treatment of the product to investigate a photoprotective effect. The phosphorylation of histone H2AX (γ-H2AX) is a direct index of DNA molecular lesion [ 30 ] and it plays an important role in the DNA repair process. Therefore, damage to the keratinocytes’ DNA was determined by an immunofluorescence analysis of γ-H2AX positive cells.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of UVB rays on the DNA damage of skin cells was evaluated in association with a pre-treatment of the product to investigate a photoprotective effect. The phosphorylation of histone H2AX (γ-H2AX) is a direct index of DNA molecular lesion [ 30 ] and it plays an important role in the DNA repair process. Therefore, damage to the keratinocytes’ DNA was determined by an immunofluorescence analysis of γ-H2AX positive cells.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study confirmed that hyperinsulinemia and hyperandrogenism share a bidirectional link, and both of them promote abnormal clock gene expression and induce granulosa cell apoptosis ( 65 ). Despite the relationship between circadian rhythm and apoptosis having been revealed in multiple cell types ( 81 , 82 ), few studies have focused on ovarian granulosa cells ( Fig. 2 ; Table 1 ).…”
Section: Chronodisruption In the Hpg Axismentioning
confidence: 99%
“…This data suggests differential roles of the clock proteins in regulating p53. These differences in p53 activity linked to the clock could be attributed to the multiple functions of p53 linked to UV stress, DNA damage response, DNA repair, or apoptosis pathways in a cell type dependent manner [6366].…”
Section: Oncogenes and Tumor Suppressors Crosstalk With The Clockmentioning
confidence: 99%